The burden of geriatric traumatic brain injury on trauma systems: Analysis of 348, 800 Medicare inpatient claims. Issue 2 (4th November 2022) - Fakhry, Samir M.; Shen, Yan; Garland, Jeneva M.; Wilson, Nina Y.; Wyse, Ransom J.; Morse, Jennifer L.; Hunt, Darrell L.; Acuna, David; Dunne, James; Kurek, Stanley J.; Gordy, Stephanie D.; Watts, Dorraine D.
Abstract: Background: Traumatic brain injury (TBI) is a leading cause of death and disability in older adults. The aim of this study was to characterize the burden of TBI in older adults by describing demographics, care location, diagnoses, outcomes, and payments in this high‐risk group. Methods: Using 2016–2019 Centers for Medicare & Medicaid Services (CMS) Inpatient Standard Analytical Files (IPSAF), patients > 65 years with TBI (>1 injury ICD‐10 starting with "S06") were selected. Trauma center levels were linked to the IPSAF file via American Hospital Association Hospital Provider ID and fuzzy‐string matching. Patient variables were compared across trauma center levels. Results: Three hundred forty‐eight thousand eight hundred inpatients (50.4% female; 87.1% white) from 2963 US hospitals were included. Level I/II trauma centers treated 66.9% of patients; non‐trauma centers treated 21.5%. Overall inter‐facility transfer rate was 19.2%; in Level I/II trauma centers transfers‐in represented 23.3% of admissions. Significant TBI (Head AIS ≥3) was present in 70.0%. Most frequent diagnoses were subdural hemorrhage (56.6%) and subarachnoid hemorrhage (30.6%). Neurosurgical operations were performed in 10.9% of patients and operative rates were similar regardless of center level. Total unadjusted mortality for the sample was 13.9%, with a mortality of 8.1% for those who expired in‐hospital, and an additional 5.8% for those discharged to hospice. Medicare payments totaled $4.91B, with the majority (73.4%) going to Level I/II trauma centers. Conclusions: This study fills a gap in TBI research by demonstrating that although the majority of older adult TBI patients in the United States receive care at Level I/II trauma centers, a substantial percentage are managed at other facilities, despite 1 in 10 requiring neurosurgical operation regardless of level of trauma center. This analysis provides preliminary data on the function of regionalized trauma care for older adult TBI care. Future studies assessing the efficacy of early care guidelines in this population are warranted.